2014
DOI: 10.1002/ps.3922
|View full text |Cite
|
Sign up to set email alerts
|

First report of resistance to acetolactate‐synthase‐inhibiting herbicides in yellow nutsedge (Cyperus esculentus): confirmation and characterization

Abstract: The results suggest a target-site alteration as the mechanism of resistance in yellow nutsedge, which accounts for the cross-resistance to other ALS-inhibiting herbicide families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“…Certain genetically modified (GM) crop plants, which may inadvertently come in the path of the herbicides (carry-over) may able to overcome the harmful effects of these herbicides [11,84,85]. Cross-resistance is another concerning issue in agriculture and related industries as some weeds and pests have acquired resistance to several herbicides, which are related by their mode of action [86][87][88]. For example, herbicides belonging to separate chemical families but within the same mode of action [e.g., acetolactate synthase (ALS) inhibitors] may acquire herbicide resistance against both the chemical families.…”
Section: Herbicide Resistancementioning
confidence: 99%
“…Certain genetically modified (GM) crop plants, which may inadvertently come in the path of the herbicides (carry-over) may able to overcome the harmful effects of these herbicides [11,84,85]. Cross-resistance is another concerning issue in agriculture and related industries as some weeds and pests have acquired resistance to several herbicides, which are related by their mode of action [86][87][88]. For example, herbicides belonging to separate chemical families but within the same mode of action [e.g., acetolactate synthase (ALS) inhibitors] may acquire herbicide resistance against both the chemical families.…”
Section: Herbicide Resistancementioning
confidence: 99%
“…Although rare, it is not unlikely that resistance could evolve in a predominantly asexually reproducing species such as yellow nutsedge. A yellow nutsedge biotype with resistance to halosulfuron has been documented in Arkansas rice production (Tehranchian et al 2014). Studies have revealed that the resistant biotype had .…”
mentioning
confidence: 99%
“…Studies have revealed that the resistant biotype had . 2,714-fold resistance to halosulfuron compared to a susceptible standard and also showed cross resistance to other acetolactate synthase (ALS) -inhibiting herbicides including imazamox, imazethapyr, bispyribac-sodium, pyrithiobac, bensulfuron, and penoxsulam (Tehranchian et al 2014). Subsequent molecular characterization revealed the presence of a target-site mutation resulting in an amino acid substitution from Trp574 to Leu (Tehranchian et al 2014).…”
mentioning
confidence: 99%
“…Chemical control, particularly with acetolactate synthase (ALS)-inhibiting herbicides, in comparison to cultural and mechanical control, has been the most effective means for managing this weed species. Recently, a nutsedge biotype identified as yellow nutsedge by a USDA plant taxonomist (Dr. Charles Bryson) exhibited resistance to several ALS-inhibiting herbicides commonly used in Arkansas rice production (Tehranchian et al 2014b).…”
mentioning
confidence: 99%